Pengaruh Ukuran Bank, Dana Pihak Ketiga, Capital Adequacy Ratio, dan Loan To Deposit Ratio Terhadap Penyaluran Kredit Pada Perusahaan Perbankan yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2015 - Adnan Adnan; Ridwan Ridwan; Fildzah Fildzah (Jurnal Dinamika Akuntansi dan Bisnis, 2016)
This study aims to examine the influence of bank size, third party funds, capital adequacy ratio, and loan to deposit ratio to lending. The samples of this research are the bank firms listed in BEI (Indonesia Stock Exchange) in 2011-2015. The Samples are collected using purposive sampling method and resulted 29 companies become theÂ  final samples. Data were collected from financial report or annual report, then data analyzed by multiple linier regression analysis.The results of this research show that (1) bank size, third party funds, capital adequacy ratio, and loan to deposit ratioÂ  simultaneously have influence for lending, (2) bank size has positive influence for lending, (3) , third party funds has positive influence for lending, (4) capital adequacy ratio has no influence for lending, and (5) loan to deposit ratio has positive influence for lending.